1968
DOI: 10.1021/ba-1968-0077.ch060
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Alkane Oxidation by Ozone

Abstract: The characteristics of the initial step in the reaction of ozone with saturated hydrocarbons have been investigated. Ozonation of cyclohexane gives initially cyclohexanol and cyclohexanone in a 3:1 ratio. Cyclohexane is oxidized 4.5 times more rapidly than cyclohexane-d 12 . The relative reactivity of primary, secondary, and tertiary hydrogens is approximately 1:13:110. The ozonation of tertiary hydrogens to tertiary alcohols occurs with 60 to 70% retention of configuration. The presence of good hydrogen atom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1969
1969
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 10 publications
(14 reference statements)
1
22
0
Order By: Relevance
“…[1][2][3][4] HTs including a wide range of O-and Si-containing compounds (alcohols, ethers, acetals, aldehydes, silanes, etc.) have been synthesized and examined since then.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] HTs including a wide range of O-and Si-containing compounds (alcohols, ethers, acetals, aldehydes, silanes, etc.) have been synthesized and examined since then.…”
Section: Introductionmentioning
confidence: 99%
“…Ozone attack on oxygen (Scheme 3c) is similar to that proposed for the ozonation of certain amines (18), and ethers (12). Finally, radical mechanisms (Scheme 3d) have been proposed for the ozonation of certain hydrocarbons (19)(20)(21) and alcohols (21) as well as ethers at high temperatures (1 1).…”
Section: Substituent Effectsmentioning
confidence: 63%
“…Studies on the properties of HOOO • revealed that the hydrotrioxy radical is a very labile species that, with high probability, decays at the HO-OO • bond. For this reason, no formation of trioxides was observed in liquid-phase oxidation of aliphatic hydrocarbons with ozone, whereas the role of ozone is likely to be limited to initiation of free radical processes according to Scheme 3 56 . Under conditions that stabilize the trioxy intermediate, the formation of hydrotrioxides is assumed 14,57,58 to involve HOOO • (and/or its conjugate anion HOOO − ) (Scheme 6).…”
Section: Hydrotrioxy Radical Hooo •mentioning
confidence: 99%